Utilizing an SBAR Workshop With Baccalaureate Nursing Students to Improve Communication Skills. Issue 2 (March 2020) - Stevens, Natalie; McNiesh, Susan; Goyal, Deepika
Abstract : Abstract: This study evaluated the effectiveness of the Situation-Background-Assessment-Recommendation (SBAR) technique to reduce anxiety and increase self-confidence levels regarding health care communication among undergraduate nursing students. Baccalaureate nursing students ( n = 35) completed anxiety and self-confidence questionnaires before and after an SBAR communication workshop and subsequent simulation. A statistically significant increase in postintervention self-confidence scores was noted with no significant difference in anxiety levels. The findings support the use of SBAR as an organizing tool to promote nursing students' self-confidence during communication; however, further efforts are needed to qualitatively examine how this tool promotes these changes.